If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -104 + 12x = 28 Reorder the terms: -104 + -1x + 12x = 28 Combine like terms: -1x + 12x = 11x -104 + 11x = 28 Solving -104 + 11x = 28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '104' to each side of the equation. -104 + 104 + 11x = 28 + 104 Combine like terms: -104 + 104 = 0 0 + 11x = 28 + 104 11x = 28 + 104 Combine like terms: 28 + 104 = 132 11x = 132 Divide each side by '11'. x = 12 Simplifying x = 12
| 2x^2+13x-57=0 | | 14(t-6)+4t=6(3t+2)-9 | | 2.6x+87=4.8x+10 | | -8(-a-4)=6(a+3) | | -6=0.75z+3 | | 4+0.3h=19 | | 21+4h=11h | | 3y-5=4+5y | | 19h+4h=126.5 | | (x+4)/6=-2 | | 9-10x+5=-28 | | 10x-16x=12 | | 4+9+5+x=2x | | x^2+6x-1=4 | | 3x+5=8x-21 | | X-6=-2+8 | | 8x-8=4x+12 | | 9c+6=15 | | -1+8(8+7n)=2+56n | | 25=4(m-3)-3 | | 4-1.8y=-5.9 | | -74+4x+3x=115 | | 15r=3(r+28) | | -44n=-4n-8(3n-5) | | 6q=24q+1 | | (4x^3-8x^2+x-5)(x^2+6x)=0 | | 5(6x+4)+1=21-3x | | 11z=20-9z | | 5.7t+2.52=52.77 | | -4.3-0.1h=-6.1 | | 2(a+6)+3a=32 | | -7.32=8.8-6.2t |